Basic electrocardiography : normal and abnormal ECG patterns - Bay s de Luna, Antoni (Blackwell Pub, 2007)
Electrocardiography is a simple investigation to perform, but accurate interpretation can be challenging. This book takes a logical and systematic approach to ECG interpretation, beginning with the basics of normal variations and dealing in turn with atrial abnormalities, ventricular enlargement, ventricular conduction defects and ischemic heart disease. Extensively illustrated with ECG tracings that complement the text, this book provides clear and concise explanations of traditional concepts of electrocardiography and combines them with updates on the most recent developments in the field. In 22 clinical cases, Professor Bayés de Luna illustrates the principles of the book by integrating electrocardiographic features with clinical findings for a thorough and methodical approach to cardiac disease. Regular self-assessments allow readers to evaluate their understanding of the ECG and reinforce key concepts. This book is an ideal introduction to normal and abnormal ECG patterns. It is particularly valuable for medical students, residents / junior doctors and nurses who wish to broaden their skills in electrocardiography.